Growing giants: ontogeny and life history of the temnospondyl Mastodonsaurus giganteus (Stereospondyli) from the Middle Triassic of Germany - Rainer R. Schoch; Florian Witzmann; Raphael Moreno; Ralf Werneburg; Eudald Mujal (Fossil Record)
The Middle Triassic capitosaur Mastodonsaurus giganteus was the largest temnospondyl and the dominating aquatic predator in many European freshwater to brackish ecosystems. It is represented by numerous size classes, which are described and analysed for the first time. The documented size range encompasses specimens between 12–15 mm and 1200 mm in skull length. Early growth stages are restricted to dentaries and interclavicles, whereas juveniles are represented by partial skulls, mandibles, and girdles. The smallest specimens already possessed diagnostic features of the taxon, and small juveniles also shared the dermal ornament with larger specimens. The heavy, disc-shaped intercentra were established early in the juvenile phase. Cranial proportions were remarkably conservative throughout ontogeny, with the orbits proportionately decreasing in size only very moderately, the postorbital skull becoming slightly longer and the occipital margin more concave in the largest forms. Analysis of frequency distributions of M. giganteus in different Lower Keuper deposits in southern Germany reflects habitat preferences in specific phases of its life cycle. The coal-bearing deposit at Gaildorf yielded unusually large specimens with relatively well-ossified appendicular skeletons. In the more common lake shore facies, only adult specimens are present. In turn, juveniles might have dwelled in calmer environments. Smaller lakes were apparently less attractive than larger or deeper water bodies that provided sufficient resources for several temnospondyls, and juvenile specimens have been identified from all of them. The diverse actinopterygian fish fauna provided prey for all growth stages of the large temnospondyl predators.